1971
DOI: 10.1002/bip.360100302
|View full text |Cite
|
Sign up to set email alerts
|

Acridine orange–poly (α‐L‐glutamic acid) complexes. I. Stoichiometry and stacking coefficients

Abstract: SynopsisBy iiieaiis of fiuoresceiicc, absorptioii, and acid-base t itrittioiis, it tias bee11 showii t 1i:tt there is a one-to-one corresporideiice between free carboxylates arid boiiiid aciiditie oiaiige in the dye-polyacid complex. Coritmry to expections, stackiiig coefticierits for 1 he dye were found t,o be virt,ually the same on binding 1.0 the helical or coiled polyacid, iiidicatirig a strong similarity in the binding sit,es for both forms of the polyelectrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Titration data were analyzed in the same manner as those reported elsewhere. [5][6][7]9 At an early stage in the titration, the spectra have a predominant peak at 492 nm. This peak corresponds to the absorption of three species: free monomer, free dimer, and bound dye.…”
Section: Resultsmentioning
confidence: 99%
“…Titration data were analyzed in the same manner as those reported elsewhere. [5][6][7]9 At an early stage in the titration, the spectra have a predominant peak at 492 nm. This peak corresponds to the absorption of three species: free monomer, free dimer, and bound dye.…”
Section: Resultsmentioning
confidence: 99%
“…These hydrophobic interactions might explain why these two monovalent CPCs bind the GAG in contrast to monovalent arginine. In support, it has been found that soluble acridine orange AOR can self-assemble when interacting with anionic polyelectrolytes or interfaces (33,43,44). It may be noted that the release of solvent water also plays a key role in binding and aggregation of polycations with other polyelectrolytes such as DNA (45)(46)(47).…”
Section: Binding Mechanismmentioning
confidence: 96%
“…Equations 12 and 13 easily reduce to the case of second neighbor (or first neighbor) interaction by setting qg = 1 (or qa = q2 = 1). The fraction of sequences of length m is25 Fm = Eiq3m-392m-2(9iu)m-1 (14) The fraction of molecules in the mth aggregate state is Xm = rnFm , (15) where, of course…”
Section: Mathematical Formalismmentioning
confidence: 99%